Using Game Theory to Analyze Strategic Tax Avoidance and Evasion Behaviors among Corporations and Individuals - Celestin, Mbonigaba; Vasuki, M.; Kumar, A. Dinesh; Asamoah, Paul Johnson (Journal of UTEC Engineering Management, 2025)
This study applies game theory to analyze strategic tax avoidance and evasion behaviors among corporations and individuals, emphasizing decision-making within regulated environments. Drawing on empirical data from tax compliance reports covering North America, Europe, Asia-Pacific, the Middle East, and Latin America between 2020 and 2024, the research employs a mixed-method approach. Quantitative models such as the Prisoner’s Dilemma and Nash Equilibrium are combined with regression, chi-square, and time-series analyses to evaluate compliance behavior and economic outcomes. Results show a strong negative correlation (-0.74) between tax evasion and economic growth, and a positive Pearson coefficient (0.75) linking corporate profitability with aggressive avoidance strategies. Compliance disparities are evident, with corporations achieving higher rates (68%) than individuals (54%), reflecting structured tax planning. Policy simulations indicate that every 1% increase in audit frequency raises compliance by 0.5%. These findings highlight the value of digital monitoring, international cooperation, and balanced deterrent-incentive mechanisms in mitigating tax avoidance and safeguarding revenue sustainability.